2008
DOI: 10.1136/gut.2008.165894
|View full text |Cite
|
Sign up to set email alerts
|

Primary eosinophilic disorders of the gastrointestinal tract

Abstract: Eosinophils are important effector cells of the innate immune system. Eosinophilic infiltrative disorders of the gastrointestinal tract, though recognised for decades, have recently witnessed a resurgence of interest, particularly for oesophageal disease. A more comprehensive basis for eosinophilic infiltration and activation has identified interleukin 5 (IL5) as a key cytokine for the differentiation and proliferation of eosinophils, while eotaxins promote the recruitment of mature eosinophils to the gut. Whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
168
0
12

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(181 citation statements)
references
References 109 publications
(136 reference statements)
1
168
0
12
Order By: Relevance
“…4,5 In children, the presentation is more variable with symptoms such as regurgitation, abdominal pain, vomiting, and failure to thrive. 4,6 EO does not affect mortality but untreated can cause oesophageal stricturing.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 In children, the presentation is more variable with symptoms such as regurgitation, abdominal pain, vomiting, and failure to thrive. 4,6 EO does not affect mortality but untreated can cause oesophageal stricturing.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Importantly, up to 23% of patients with primary EGID have no peripheral eosinophilia. 7 Symptoms and signs of EGID are usually non-specific and, depending on the affected segment, include abdominal pain, nausea, vomiting, diarrhea, gastrointestinal bleeding, obstruction, malabsorption, weight loss, and ascites.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of EoE is much higher in Western countries compared to Asia, including Japan. In contrast, EGE is relatively common in the Asian population compared to the Western population [10][11][12]. A recent systematic review by Arias et al [13] revealed that the population-based prevalence of EoE was estimated at 2.3-56.3/100,000, with a combined prevalence of 22.7/ 100,000 and 0.28% in North American and European populations.…”
Section: Epidemiologymentioning
confidence: 99%
“…In EoE, eosinophilic inflammation is localized to the esophagus; however, in the EGE or EC, it can extend to the entire gastrointestinal tract from the esophagus to the rectum [10]. EoE has been recognized as a clinicopathological disease characterized by both esophageal symptoms and histologically proven EE.…”
Section: Definitionmentioning
confidence: 99%